2018
DOI: 10.1016/j.jth.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Sub-population differences in the relationship between the neighborhood environment and Latinas' daily walking and vehicle time

Abstract: Latinas participated in relatively low walking time and high amounts of vehicle time. Findings suggest intrapersonal sub-group differences in the association of the neighborhood environment with walking and vehicle time. Improving neighborhood environments to promote walking and reduce vehicle time may help improve Latinas' overall physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…The former hypothesised that the objective built environment influenced walking through perceived environment (Ma and Cao 2017;Orstad et al 2017); while the latter proposed that the relationships between objective environment and walking depends on the perceived environment. For instance, some recent studies have explored various moderation effects between neighbourhood environment and physical activity through psychosocial factors (Serrano et al 2018;Perez et al 2016), and walking attitudes (Yang and Diez-Roux 2017). However, the effects of perceived environment in moderating the relationships between objective neighbourhood characteristics and three types of walking frequency are understudied and deserve more structured examination.…”
Section: Environmental Influence On Walking Behaviourmentioning
confidence: 99%
“…The former hypothesised that the objective built environment influenced walking through perceived environment (Ma and Cao 2017;Orstad et al 2017); while the latter proposed that the relationships between objective environment and walking depends on the perceived environment. For instance, some recent studies have explored various moderation effects between neighbourhood environment and physical activity through psychosocial factors (Serrano et al 2018;Perez et al 2016), and walking attitudes (Yang and Diez-Roux 2017). However, the effects of perceived environment in moderating the relationships between objective neighbourhood characteristics and three types of walking frequency are understudied and deserve more structured examination.…”
Section: Environmental Influence On Walking Behaviourmentioning
confidence: 99%
“…Other factors include characteristics and constraints related to families and households, policies, and elements of the social environment (Sallis et al, 2006). These layers of environmental influence help to explain why standard physical environment-focused measures of walkability, and their usefulness for predicting behavior, may vary across socioeconomic and sociocultural contexts (Adkins et al, 2017; Day, 2006; Frank et al, 2008; Sallis et al, 2009; Serrano et al, 2018). A review of studies from the fields of public health, planning, and transportation showed that the effect of a walkable physical environment on walking and physical activity was about half as strong for low-income, people of color, and those with lower educational attainment than for relatively socioeconomically advantaged groups (Adkins et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Esto tendría una extensión a los comportamientos de viaje, según ha sido mostrado en el caso estadounidense (Cain y Flynn, 2013). De forma más particular, también se ha señalado en el caso de Estados Unidos que los niveles mayores de educación se traducen en un uso más intenso del automóvil (Serrano et al, 2018), o en la preferencia por sistemas de transporte público de alta calidad como el tren ligero (Cain y Flynn, 2013). En el otro lado del espectro social, los estratos bajos, ante los elevados niveles de inseguridad, no pueden dejar de usar el transporte público, pues no tienen recursos suficientes para encontrar alternativas económicas de viaje, según han documentado Halat et al (2015) para el caso estadounidense.…”
Section: Discussionunclassified